2011
DOI: 10.1177/147323001103900127
|View full text |Cite
|
Sign up to set email alerts
|

Renal Haemodynamics in Patients with Liver Cirrhosis Assessed by Colour Ultrasonography

Abstract: Colour Doppler flow imaging was used in this prospective, cross-sectional study to analyse renal haemodynamics in 50 cirrhotic patients and 15 healthy controls. Mean renal arterial resistive index (RI) was higher in cirrhotic patients than in healthy controls. Mean RI was also higher in cirrhotic patients with non-refractory ascites than in those without ascites, suggesting that the degree of renal vasoconstriction varies with the severity of ascites. A gradient of RI values across the main renal artery, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Many authors have demonstrated a positive correlation between high pretransplant RI (.0.70), post-transplant morbidity and a poor outcome. 41 In conclusion, high RI ($0.78) is an extremely sensitive and specific parameter for the early identification of high-risk patients of HRS, and DUS is a useful HRS tool.…”
Section: Cirrhosis and Hepatorenal Syndromementioning
confidence: 89%
“…Many authors have demonstrated a positive correlation between high pretransplant RI (.0.70), post-transplant morbidity and a poor outcome. 41 In conclusion, high RI ($0.78) is an extremely sensitive and specific parameter for the early identification of high-risk patients of HRS, and DUS is a useful HRS tool.…”
Section: Cirrhosis and Hepatorenal Syndromementioning
confidence: 89%
“…Doppler ultrasound measurement of intrarenal resistance can estimate renal blood flow and correlates with portal pressure [19]. Some studies have shown that intrarenal RIs are significantly increased in cirrhotic patients compared with healthy controls and are even higher in patients with ascites than in patients without ascites [9,10]. Patients with decompensated cirrhosis but normal serum creatinine can already present with elevated RIs [12].…”
Section: Discussionmentioning
confidence: 99%
“…It is routinely used to diagnose transplant rejection or renal artery stenosis [7,8]. Increased intrarenal RIs in patients with liver cirrhosis, especially in the decompensated stage, have been described before as compared to healthy controls [9,10,11,12,13]. Cirrhotic patients with elevated intrarenal RIs tend to develop the HRS, leading to a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Renal resistive index (RI) is usually elevated in cirrhotic patients compared to healthy individuals, and is higher in patients with ascites . An increased renal RI correlates with the risk of renal impairment in patients with normal serum creatinine, but does not always correlate with GFR value .…”
Section: Evidence Acquisitionmentioning
confidence: 99%